2021
DOI: 10.1371/journal.pone.0246582
|View full text |Cite
|
Sign up to set email alerts
|

A CT radiomics analysis of COVID-19-related ground-glass opacities and consolidation: Is it valuable in a differential diagnosis with other atypical pneumonias?

Abstract: Purpose To evaluate the discrimination of parenchymal lesions between COVID-19 and other atypical pneumonia (AP) by using only radiomics features. Methods In this retrospective study, 301 pneumonic lesions (150 ground-glass opacity [GGO], 52 crazy paving [CP], 99 consolidation) obtained from nonenhanced thorax CT scans of 74 AP (46 male and 28 female; 48.25±13.67 years) and 60 COVID-19 (39 male and 21 female; 48.01±20.38 years) patients were segmented manually by two independent radiologists, and Location, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 25 publications
3
18
0
Order By: Relevance
“…The model showed that a combination of radiomics and a basic inflammatory index obtained at admission can predict ICU admission. According to Gülbay et al [ 130 ] COVID-19 and atypical pneumonia-associated GGO lesions and consolidation could be predicted with high accuracy (80% in COVID-19 and 81% in atypical pneumonia). Roundness and peripheral location were found to be the most effective characteristics for identifying a GGO lesion with COVID-19, but were both ineffective in predicting lesions in the consolidation stage.…”
Section: Clinical Impact Of Ai-based Covid-19 Studiesmentioning
confidence: 99%
“…The model showed that a combination of radiomics and a basic inflammatory index obtained at admission can predict ICU admission. According to Gülbay et al [ 130 ] COVID-19 and atypical pneumonia-associated GGO lesions and consolidation could be predicted with high accuracy (80% in COVID-19 and 81% in atypical pneumonia). Roundness and peripheral location were found to be the most effective characteristics for identifying a GGO lesion with COVID-19, but were both ineffective in predicting lesions in the consolidation stage.…”
Section: Clinical Impact Of Ai-based Covid-19 Studiesmentioning
confidence: 99%
“…Radiomics features can be further integrated into machine learning models with the aim to improve diagnosis and patient management. This approach was recently investigated to improve the detection and the differential diagnosis of COVID-19 pneumonia 20 , 21 , 23 , 24 , 26 29 . For example, Zhang et al proposed a CT-based deep learning integrated radiomics model for the differentiation of COVID-19 pneumonia from other community acquired pneumonias.…”
Section: Introductionmentioning
confidence: 99%
“…Pleural effusion may also occur in cases of COVID-19, but is less common than the other lesions. It is therefore important to point out some difficulties with this approach, as follows: Although the features of COVID-19 are found in most cases, CT images of some viral pneumonias also show these features, which can ultimately make diagnosis more difficult [2] ; In some cases of COVID-19, biopsies are needed [3] ; Correct classification is required between healthy and diseased regions, especially those with COVID-19 and other more serious diseases such as lung nodules; and According to [4] , [5] , COVID-19 regions are generally more rounded in shape. …”
Section: Introductionmentioning
confidence: 99%
“…According to [4] , [5] , COVID-19 regions are generally more rounded in shape.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation